Pemberdayaan Masyarakat melalui Media Digital: Optimalisasi Smart Digital Marketing Berbasis Aplikasi untuk Penguatan Usaha Lokal Warga Ngampel Kulon - Akhmad Choirur Rozikin; Achmad Ziaulhaq; Khoirum Azura; Alfina Fauziyah; Siti Durorun Naja; Abdurrahman Nafis; Retno Anggi Setyowati; Revlia Ailsa Julian (Lembaga Pengembangan Kinerja Dosen, 2024)
The advancement of digital technology has revolutionized marketing from traditional methods to online approaches. Digital marketing, leveraging digital media and the internet, including e-commerce and social media, has become a crucial element in promoting products and services. According to Kotler and Keller (2023), digital marketing not only boosts sales but also strengthens brand identity and fosters customer relationships. In Indonesia, Micro, Small, and Medium Enterprises (MSMEs), which significantly contribute to the local economy, can utilize digital marketing to expand their market reach and improve efficiency. This study was conducted in Ngampel Kulon Village, Kendal Regency, Central Java, focusing on MSME operators and aspiring entrepreneurs who have not fully utilized digital platforms such as WhatsApp Business. The research method involved observation, economic potential identification, and training using a Participatory Rural Approach. The training covered four main components: an introduction to digital marketing basics, copywriting techniques, digital marketing strategies, and hands-on practice with guidance. Results showed that 34 local residents and 15 KKN students exhibited high enthusiasm and successfully applied promotional strategies through social media. The evaluation indicated an improvement in knowledge and skills in using WhatsApp Business for product marketing. The conclusion is that the training successfully enhanced MSMEs' understanding and skills in digital marketing, including digital content creation and social media utilization. The program also emphasizes the need for policy makers' involvement in planning and managing local product marketing to compete globally and adapt to ongoing technological trends.